Factors Influencing Spinal Anesthesia. Issue 1 (January 1982) - Moore, Daniel C.
Abstract : The present report is part of a randomized double-blind study of characteristics of bupivacaine and tetracaine. The following variables affecting analgesia are reported: When a 26-gauge Greene point needle was employed, no cephalalgia resulted. In a high percentage of patients, the spinal needle is not placed at the predetermined interspace. Needle gauge and cerebrospinal fluid variations do not alter the incidence of satisfactory analgesia. The height and weight of the patient, whether the solution contains 0.2 mg of epinephrine, and the position of the patient when the spinal block is performed, determine the dermatome level and quality of anesthesia. Hypotension is directly related to the dosage of the local anesthetic drug and the dermatome level of analgesia.